"Where's my right that was here?" – Between insurgent concepts and praxis of persons with disabilities and their human rights (Research, Society and Development, 2021)
The essay, in the light of critical theories of social sciences – particularly the sociology of Bauman and Sousa Santos as well as Foucault's political understanding – tends to examine the process of gradual deconstruction of social rights observed in the contemporary globalized world, particularly its mediate effects on the existential territories of vulnerable populations. Using the concepts and praxis that are central to the categories of critical emancipation, self-advocacy and subject of sanitary law, we analyze the dismantling of social welfare policies and the systematic advance of neoliberalism around the world. The essay seeks to point out insurgent emancipatory alternatives for people with disabilities and/or their social movements in confronting the (mis)paths engendered by erosive forces in the social fabric that make human existence invisible and expose it to a stigmatizing process of societal exclusion.